1996
DOI: 10.1111/j.1365-2044.1996.tb07651.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epidural blockade on gastric intramucosal pH in the peri‐operative period

Abstract: SummaryThe significance qf these results is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
0
20
0
3
Order By: Relevance
“…3 , 4 The risk of developing gut ischemia and multiple organ failure (MOF) has been recognised in patients undergoing major surgery. 5 The systemic hemodynamic effects of infrarenal aortic cross-clamping during abdominal aortic surgery are unfavourable, 6 -8 because clamping increases myocardial work and reduces cardiac output. 9 In addition, the splanchnic region appears to play a pivotal role in the development of MOF in patients undergoing major surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 , 4 The risk of developing gut ischemia and multiple organ failure (MOF) has been recognised in patients undergoing major surgery. 5 The systemic hemodynamic effects of infrarenal aortic cross-clamping during abdominal aortic surgery are unfavourable, 6 -8 because clamping increases myocardial work and reduces cardiac output. 9 In addition, the splanchnic region appears to play a pivotal role in the development of MOF in patients undergoing major surgery.…”
mentioning
confidence: 99%
“…1 0 Patients who suffer perioperative splanchnic ischemia have a poor outcome. 5 The central role of the gastrointestinal tract in the development of MOF suggests that outcome can be improved if gut ischemia is prevented by techniques which improve splanchnic blood flow. 1 1 It has been demonstrated that epidural anesthesia has a beneficial effect on bowel function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] In addition, studies carried out on animals and humans have demonstrated that epidural anesthesia with local anesthetics during surgical stimulation maintains intestinal mucosal blood flow and gastric mucosal pH at physiological levels comparable with controls treated with general anesthetics. [11][12][13] It has been hypothesized that the increased mucosal flow can promote anastomotic healing. [14] In fact, retrospective cohort controlled studies suggest that regional anesthetic techniques are associated with a beneficial effect on anastomotic healing rates.…”
Section: Resultsmentioning
confidence: 99%
“…[14] In fact, retrospective cohort controlled studies suggest that regional anesthetic techniques are associated with a beneficial effect on anastomotic healing rates. [10][11][12][13][14][15] The stimulatory effect of epidural anesthesia on gastrointestinal mobility can lead to theoretical concern about increasing anastomotic leakage, but segmental autonomic blockade may increase the blood supply to the anastomosis and improve healing. In a recently published meta-analysis, the rate of anastomotic leakage remained the same, regardless of the analgesic technique used.…”
Section: Resultsmentioning
confidence: 99%